Push-Out Test and Hysteretic Performance Study of Semi-Rigid Shear Keys with the Triple-Folded Web of Flange - Zhenshan Wang; Huaqian Qin; Yong Yang; Yunhe Liu; Hongchao Guo; Hongchen Wang (Buildings, 2022)
The PBL (Perfobond Leiste) shear connector has the advantages of high bearing capacity and strong constraint ability; however, the traditional PBL shear connector has strong and weak axis problems, and its stiffness is large, resulting in weak deformation ability. To this end, this paper proposes a new type of flange triple-web shear key and obtains the new shear key’s mechanical properties and failure mechanism through the push-out test. The results show that the failure mode of the new shear key is the deformation of the steel plate on the web and the edge of the opening, which has a high bearing capacity, outstanding deformation ability, and good integrity with concrete, showing obvious semi-rigid characteristics. Through numerical analysis, the effects of flange width, web height, and steel plate thickness on the mechanical properties of shear keys are obtained. Based on the fitting analysis method, the calculation formula of shear key bearing capacity is proposed. Finally, the horizontal seismic performance of the shear key is numerically simulated. It is found that the hysteretic curve of the shear key is full and shows good energy dissipation capacity.